Novel Approach to Abstract the Data Flow Diagram from Java Application Program - Kulkarni, R. N.; Prasad, P. Pani Rama (International Journal of Intelligent Systems and Applications in Engineering, 2023)
During the years 1920 to 1930, business processes came into use and they used flow charts for documenting the process flow. Further, it was developed as a flow chart to plan flow of information in computer programs. During 1960’s onwards the designer of computer programs used algorithms and flow charts for the representation of the software design. In the year 1970, the Data Flow Diagram (DFD) was introduced, which depict the structured analysis and the data modeling. In this paper, a methodology is proposed and a tool is developed that is used to abstract complete DFD from given java program. The proposed abstraction is carried out with the help of following steps. First step, restructure the input java program that is amenable for the abstraction of DFD components. Second step, Identifying the input attributes set and output attributes set, data flow, different process, entities and data store. Third step, representing the abstracted components in the table format. Next step, redesigning the data flow diagram from the input DFD table.